Meningococcal factor H binding proteins in epidemic strains from Africa: implications for vaccine development. - Rolando Pajon; Andrew M Fergus; Oliver Koeberling; Dominique A Caugant; Dan M Granoff (Public Library of Science (PLoS), 2011)
Factor H binding protein (fHbp) is an important antigen for vaccines against meningococcal serogroup B disease. The protein binds human factor H (fH), which enables the bacteria to resist serum bactericidal activity. Little is known about the vaccine-potential of fHbp for control of meningococcal epidemics in Africa, which typically are caused by non-group B strains.We investigated genes encoding fHbp in 106 serogroup A, W-135 and X case isolates from 17 African countries. We determined complement-mediated bactericidal activity of antisera from mice immunized with recombinant fHbp vaccines, or a prototype native outer membrane vesicle (NOMV) vaccine from a serogroup B mutant strain with over-expressed fHbp. Eighty-six of the isolates (81%) had one of four prevalent fHbp sequence variants, ID 4/5 (serogroup A isolates), 9 (W-135), or 74 (X) in variant group 1, or ID 22/23 (W-135) in variant group 2. More than one-third of serogroup A isolates and two-thirds of W-135 isolates tested had low fHbp expression while all X isolates tested had intermediate or high expression. Antisera to the recombinant fHbp vaccines were generally bactericidal only against isolates with fHbp sequence variants that closely matched the respective vaccine ID. Low fHbp expression also contributed to resistance to anti-fHbp bactericidal activity. In contrast to the recombinant vaccines, the NOMV fHbp ID 1 vaccine elicited broad anti-fHbp bactericidal activity, and the antibodies had greater ability to inhibit binding of fH to fHbp than antibodies elicited by the control recombinant fHbp ID 1 vaccine.NOMV vaccines from mutants with increased fHbp expression elicit an antibody repertoire with greater bactericidal activity than recombinant fHbp vaccines. NOMV vaccines are promising for prevention of meningococcal disease in Africa and could be used to supplement coverage conferred by a serogroup A polysaccharide-protein conjugate vaccine recently introduced in some sub-Saharan countries.